Use of Google EarthTM to strengthen public health capacity and facilitate management of vector-borne diseases in resource-poor environments - Lozano Fuentes, Saúl; Elizondo Quiroga, Darwin; Farfán Ale, José Arturo; Loroño Pino, María Alba; García Rejón, Julián Everardo; Gomez Carro, Salvador; Lira Zumbardo, Victor; Nájera Vázquez, María del Rosario; Fernández Salas, Ildefonso; Calderón Martínez, Joaquín; Domínguez Galera, Marco Antonio; Mis Ávila, Pedro; et al. (World Health Organization, 2008)
OBJECTIVE: Novel, inexpensive solutions are needed for improved management of vector-borne and other diseases in resource-poor environments. Emerging free software providing access to satellite imagery and simple editing tools (e.g. Google EarthTM) complement existing geographic information system (GIS) software and provide new opportunities for: (i) strengthening overall public health capacity through development of information for city infrastructures; and (ii) display of public health data directly on an image of the physical environment. METHODS: We used freely accessible satellite imagery and a set of feature-making tools included in the software (allowing for production of polygons, lines and points) to generate information for city infrastructure and to display disease data in a dengue decision support system (DDSS) framework. FINDINGS: Two cities in Mexico (Chetumal and Merida) were used to demonstrate that a basic representation of city infrastructure useful as a spatial backbone in a DDSS can be rapidly developed at minimal cost. Data layers generated included labelled polygons representing city blocks, lines representing streets, and points showing the locations of schools and health clinics. City blocks were colour-coded to show presence of dengue cases. The data layers were successfully imported in a format known as shapefile into a GIS software. CONCLUSION: The combination of Google EarthTM and free GIS software (e.g. HealthMapper, developed by WHO, and SIGEpi, developed by PAHO) has tremendous potential to strengthen overall public health capacity and facilitate decision support system approaches to prevention and control of vector-borne diseases in resource-poor environments.